Bamboo Improvement Works in Arunachal Pradesh - Beniwal, B. S.; Singh, N. B. (Indian Forester, 1988)
Arunacbal Pradesh Is very rich in bamboo having more than 30 species in wilderness. Bamboo is used by the tribal people for a variety of purposes and is very much linked with their socio-economic needs. Keeping in view the importance of bamboo, its improvement work was taken up in Arunachal Pradesh during 1980 with the objective to establish germ-plasm banks of improved materials and to multiply it for supplling to the villagers. Eight important species of bamboos were taken up and plus bamboo were selected from the bamboo grown in the villages and also from natural forests. Offsets were purchased from the villagers and bamboo germ-plasm banks were established during 1984 over 6 hectares at Chessa and Namsai. Among the plus bamboo BB/CH-4, BT/NS-13, BT/CH-7, BP/CH-3, BP/CH-7, BN/CH-I, Nangal CH-2 and CH-4 bave shown superiority over other plus bamboo.